Development of Lkpd Nature Science with The Etno-Stem Approach to The Processing of Gambier on Additive Material at The District Junior High Shool 50 City - Ezimon, Azahra; Diliarosta, Skunda (Department of Science Education, 2024)
This study aims to determine the validity and practicality of LKPD IPA with the Ethno-Stem Approach in the process of processing gambier in additive materials at Fifty City Middle Schools. This research is a Research and Development (R&D) with a 4-D development model. The instruments used in this study were validity and practicality questionnaires. LKPD has been validated by an expert validator using a validity questionnaire. The practicality test was carried out by teachers and students using a product practicality questionnaire to obtain validity with an average of 0.79 in the valid category. The average value of the practicality of using the Ethno-Stem Approach IPA practical worksheets in the gambier processing of additive material at the Fifty City Middle School District, according to teachers and students, was 0.88 and 0.93, respectively, belonging to the very practical category. So it can be concluded that the practicality of LKPD IPA with the Ethno-Stem Approach in the processing of gambier on additive material at Fifty City Middle School District is valid and practical to use